Atypical Perinuclear Antineutrophil Cytoplasmic Antibodies in Patients with Crohn’s Disease - Hugh J Freeman (Canadian Journal of Gastroenterology)
Atypical perinuclear antineutrophil cytoplasmic antibodies (p-ANCA) occur in most patients with ulcerative colitis but only in a minority of those with Crohn's disease. In a recent study from the United States, this serological marker was reported to be present in 100% of Crohn's disease patients with a clinical phenotype of 'left-sided ulcerative colitis' but was not present in patients with 'isolated' small bowel disease. In a previously reported survey from the author's hospital, the p-ANCA status of 247 consecutive patients with Crohn's disease was evaluated, and, of these, 33 Crohn's disease patients were seropositive, including 18 (13.0%) with combined small and large bowel disease, 11 (19.6%) with 'isolated' colorectal disease, and four (4.6%) with 'isolated' small bowel but no detectable colorectal disease. To further evaluate and verify the significance of atypical p-ANCA in these 33 patients, clinical, radiological, endoscopic and histological features were examined. This study confirms that an 'ulcerative colitis-like' clinical phenotype may be seen in most, but not all, serologically positive Crohn's disease patients. Moreover, 'isolated' small bowel disease in the absence of colorectal disease occurs. Detection of atypical p-ANCA in Crohn's disease with different clinical and pathological features provides serological evidence that Crohn's disease is a very heterogeneous disorder.